PONTOS CONTROVERSOS NA APLICAÇÃO DO IRDR (Reflection and Critique Law Magazine, 2024)
Among the numerous innovations of the 2015 Code of Civil Procedure, the brazilian procedure for repetitive claims, the IRDR, provided for in art. 976 et seq. of the aforementioned Code. The innovative mechanism in the national system was inspired by foreign mechanisms, having as its main objective to contingency the repetitive demands that plague the judiciary, by setting a binding thesis that will be applied to all processes with the same repetitive issue affected by the procedure, within the jurisdiction territory of the court that judged it and established the IRDR thesis. Divergences and controversies hover over the institute even before the approval of the code, some of which have been improved and developed in practical application before the courts. The present work demonstrates an overview of the application of the IRDR, addressing the main controversial points related to the topic, such as which judgment technique should be applied to the pilot cause or model procedure, the hypotheses and assumptions of appropriateness, suspension and suspension of the processes, the possibility of distinction, the national expansion of the suspension, the granting of provisional protection, the modulation of the suspension effect and the appropriate resources in light of empirical data, doctrine and jurisprudence.